2014
DOI: 10.32421/juri.v21i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Doxazosin and Meloxicam Combination Therapy for BPH Treatment With Luts

Abstract: Objective: To compare the efficacy of combination therapy of 4 mg doxazosin + 15 mg meloxicam with 4 mg doxazosin single therapy for benign prostate hyperplasia (BPH) patients with lower urinary tract symptoms (LUTS). Materials & Methods: A prospective, randomized and double blind study with total of 22 BPH patients with LUTS were randomized to receive 4 mg doxazosin + placebo once daily for 6 weeks or a combination of 4 mg doxazosin + 15 mg meloxicam once daily for 6 weeks. Inclusion criteria included IPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…24 Combination therapy of meloxicam 15 mg and doxazosin 4 mg per oral once daily for six weeks was better in increasing Qmax and decreasing prostate blood flow in BPH patients with LUTS. 19 In a systematic review and meta-analysis of NSAIDs effects in LUTS BPH patient it was concluded that there were improvements in LUTS and urinary emissions as a result of NSAID administration. No serious adverse effects found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Combination therapy of meloxicam 15 mg and doxazosin 4 mg per oral once daily for six weeks was better in increasing Qmax and decreasing prostate blood flow in BPH patients with LUTS. 19 In a systematic review and meta-analysis of NSAIDs effects in LUTS BPH patient it was concluded that there were improvements in LUTS and urinary emissions as a result of NSAID administration. No serious adverse effects found.…”
Section: Discussionmentioning
confidence: 99%
“…18 Combination of oral meloxicam 15 mg and doxazosin 4 mg once daily for six weeks increase the maximum urine flow rate (Qmax) and decrease prostate blood flow in BPH patients with LUTS. 19 A systematic review and meta-analysis of non steroid anti-inflammation drugs (NSAID) effect by Kahokehr et al (2013) concluded that there were improvements in LUTS and urinary emissions as a result of NSAID administration. No serious adverse effects on NSAID administration is shown.…”
Section: Introductionmentioning
confidence: 99%